Assessing the asymptomatic reservoir and dihydroartemisinin–piperaquine effectiveness in a low transmission setting threatened by artemisinin resistant Plasmodium falciparum. (December 2016) - Falq, Grégoire; Bergh, Rafael; Smet, Martin; Etienne, William; Nguon, Chea; Rekol, Huy; Imwong, Mallika; Dondorp, Arjen; Kindermans, Jean-Marie
Abstract Background In Cambodia, elimination of artemisinin resistance through direct elimination of thePlasmodium falciparum parasite may be the only strategy. Prevalence and incidence at district and village levels were assessed in Chey Saen district, Preah Vihear province, North of Cambodia. Molecular and clinical indicators for artemisinin resistance were documented. Methods A cross sectional prevalence survey was conducted at village level in the district of Chey Saen from September to October 2014.Plasmodium spp. was assessed with high volume quantitative real-time polymerase chain reaction (qPCR).Plasmodium falciparum -positive samples were screened for mutations in thek13 -propeller domain gene. Treatment effectiveness was established after 28 days (D28) using the same qPCR technique. Data from the provincial surveillance system targeting symptomatic cases, supported by Médecins Sans Frontières (MSF), were used to assess incidence. Results DistrictP. falciparum prevalence was of 0.74 % [0.41; 1.21]; village prevalence ranged from 0 to 4.6 % [1.4; 10.5]. The annual incidence ofP. falciparum was 16.8 cases per 1000 inhabitants in the district; village incidence ranged from 1.3 to 54.9 for 1000 inhabitants. Two geographical clusters with high number of cases were identified by both approaches. The marker for artemisinin resistance was found in six samples out of the 11 tested (55 %). 34.9 % of qPCR blood analysis of symptomatic patients were still positive at D28. Conclusions The overall low prevalence ofP. falciparum was confirmed in Chey Saen district in Cambodia, while there were important variations between villages. Symptomatic cases had a different pattern and were likely acquired outside the villages. It illustrates the importance of prevalence surveys in targeting interventions for elimination. Mutations in thek13 -propeller domain gene (C580Y), conferring artemisinin resistance, were highly prevalent in both symptomatic and asymptomatic cases (realizing the absolute figures remain low). Asymptomatic individuals could be an additional reservoir for artemisinin resistance. The low effectiveness of dihydroartemisinin–piperaquine (DHA–PPQ) for symptomatic cases indicates that PPQ is no longer able to complement the reduced potency of DHA to treat falciparum malaria and highlights the need for an alternative first-line treatment.